ՀՀ-ում արդյունավետ գործառող սոցիալական պաշտպանության համակարգի ստեղծման հնարավորությունները - Յարմալոյան, Մարինե (Bulletin of Yerevan University G: Economics, 2017)
The article presents the main problems impeding the formation of effective functioning social protection system in RA. The author also suggests possible solutions to those problems.
Keywords: social protection system, social protection subsystem, social protection concept, social protection object, social protection subject